Heterologous Expression, Purification, and Immunomodulatory Effects of Recombinant Lipoprotein GUDIV-103 Isolated from Ureaplasma diversum - Manoel Neres Santos-Junior; Wanderson Souza Neves; Ronaldo Silva Santos; Palloma Porto Almeida; Janaina Marinho Fernandes; Bruna Carolina de Brito Guimarães; Maysa Santos Barbosa; Lucas Santana Coelho da Silva; Camila Pacheco Gomes; Beatriz Almeida Sampaio; Izadora de Souza Rezende; Thiago Macedo Lopes Correia; et al. (Microorganisms, 2022)
Ureaplasma diversum is a bacterial pathogen that infects cattle and can cause severe inflammation of the genital and reproductive systems. Lipid-associated membrane proteins (LAMPs), including GUDIV-103, are the main virulence factors in this bacterium. In this study, we heterologously expressed recombinant GUDIV-103 (rGUDIV-103) in Escherichia coli, purified it, and evaluated its immunological reactivity and immunomodulatory effects in bovine peripheral blood mononuclear cells (PBMCs). Samples from rabbits inoculated with purified rGUDIV-103 were analysed using indirect enzyme-linked immunosorbent assay and dot blotting to confirm polyclonal antibody production and assess kinetics, respectively. The expression of this lipoprotein in field isolates was confirmed via Western blotting with anti-rGUDIV-103 serum and hydrophobic or hydrophilic proteins from 42 U. diversum strains. Moreover, the antibodies produced against the U. diversum ATCC 49783 strain recognised rGUDIV-103. The mitogenic potential of rGUDIV-103 was evaluated using a lymphoproliferation assay in 5(6)-carboxyfluorescein diacetate succinimidyl ester–labelled bovine PBMCs, where it induced lymphocyte proliferation. Quantitative polymerase chain reaction analysis revealed that the expression of interleukin-1β, toll-like receptor (TLR)-α, TLR2, TLR4, inducible nitric oxide synthase, and caspase-3–encoding genes increased more in rGUDIV-103–treated PBMCs than in untreated cells (p < 0.05). Treating PBMCs with rGUDIV-103 increased nitric oxide and hydrogen peroxide levels. The antigenic and immunogenic properties of rGUDIV-103 suggested its suitability for immunobiological application.